Synthesis and Performance of Sulfonated Poly (Arylene Ether Sulfone) as Proton Exchange Membrane (Journal of Fiber Bioengineering and Informatics, 2012)
A series of novel sulfonated poly(arylene ether sulfone) (SPAES) were prepared by aromatic nucleophilicsubstitution polycondensation from 4, 4'-dichlorodiphenylsulfone (DCDPS), 3, 3'-disulfonated-4, 4'-dichlorodiphenylsulfone (SDCDPS) and 4-fluorophenyl hydroquinone and characterized by viscositymeasurement, FT-IR, ^1H-NMR and TG. The SPAES membranes consisting of different ratio of SDCDPSto DCDPS were cast from their solutions. The alternating current (AC) proton conductivity of SPAESmembranes were carried on. The values of inherent viscosity ranging from 1.04 to 2.43 dl/g, implying thatSPAESs possessed high molecular weight. The results of TG analysis showed SPAESs were thermal stableup to nearly 200 °C. The acid forms (H^+) of SPAES films were tough and ductile with the tensile strengthof 61-91 Mpa. The proton conductivity of SPAES films became higher with the increasing content ofSDCDPS in chain composition. SPAES with 50% SDCDPS showed the highest proton conductivityof 0.205 S/cm at 80 °C. The water uptake and dimension swelling of SPAES membranes were alsomeasured. At the same time, SPAES showed excellent proton transportation stability when used at hightemperature. SPAESs had a higher water uptake than Nafion 115, while experimental IEC of SPAESsin the range of 0.77-1.35 meq/g at 80 °C were very closed to the calculated ones.
Keywords: Sulfonated Poly(Arylene ether Sulfone); Proton Conductivity; IEC; PEM